The use of thromboaspiration and combined treatment in patients with ischemic stroke in real-life clinical practice - T. V. Volchenkova; S. V. Kotov; E. V. Isakova; M. V. Sutormin; E. V. Patrin; B. B. Gegenava; M. N. Martynovich; I. G. Rudakova; L. V. Smetana; V. A. Borisova; S. V. Belkina (Неврология, нейропсихиатрия, психосоматика)
The effectiveness of staged reperfusion therapy in real clinical practice requires clarification. Objective: to evaluate the efficacy and safety of mechanical thromboextraction and staged reperfusion therapy with alteplase in real clinical practice. Material and methods. The study included 106 patients who were retrospectively divided into two groups: Group I underwent staged reperfusion therapy (intravenous thrombolysis with alteplase followed by aspiration thromboextraction), Group II underwent thromboaspiration only. The clinical and functional results, incidence of hemorrhagic transformation and mortality rate were compared. Results. The groups did not differ in terms of demographic data, cardiovascular risk factors or stroke severity. Group II patients were characterized by a longer delay in reperfusion therapy (225 minutes versus 180 minutes) and a lower score on the Alberta Stroke Programme Early CT score (ASPECTS; 8.8 points versus 9.3 points). There were no differences in National Institutes of Health Stroke Scale (NIHSS) scores at day 28, dynamics of NIHSS scores, Rankin scores at day 28, rates of hemorrhagic transformation or mortality. In both groups, the deceased patients were older; in Group I they suffered more frequently from atrial fibrillation, in Group II – from diabetes mellitus type 2. In addition, mortality in Group II was associated with a higher severity of early signs of cerebral infarction.Conclusion. The results of the analysis of real-life clinical practice show the comparability of the efficacy and safety of staged reperfusion therapy and isolated thromboaspiration in a “natural” selection of patients.